Banco de entrenamiento electroneumático para el área de automatización de la universidad Antonio Nariño (2020)
The general objective of the project is to build an electropneumatic training bench and PLC that allows the strengthening of the installed capacity in equipment for the development of practices and learning environments in industrial automation at the Antonio Nariño University. In the construction of the electropneumatic bench, the support structure was developed, in relation to the functional aspect, the easy assembly, disassembly and the design of different test circuits and sequential electrical processes. These activities effectively develop real knowledge of electro pneumatics used in production processes in the country's industrial sector.